Role of Government İnitiatives in Promoting Digitalization to Support Startup Ecosystem and Budding Entrepreneurs in India - Hardi Nanavati, Dr. Madhura Bedarkar (International Journal of Advanced Science and Technology, 2020)
Entrepreneurship and startup culture are considered as the growth engine for a country. It is gaining a lot of attention not only in India but also in other parts of the world. The startup ecosystem has developed drastically in India. Startups not only solves issues pertaining to unemployment and poverty but provides impactful and affordable solutions and thereby ensuring transformation. Entrepreneurship is not new to India; in fact, the scriptures and history of India testifies that entrepreneurial mindset is prevalent in Indian culture since ages. And with demographic transition, technological advancements, government initiatives and conducive operating environment, Startup ecosystem in India has reached unprecedented levels. Since technology has become an integral part of the business ecosystem and digitalization has become a new norm, the Government of India has undertaken some notable digital initiatives to promote Indian startup ecosystem. These digital initiatives have helped to enable, establish and enhance startups in India. Therefore, effort is done to study the role of government’s digital initiatives in supporting Indian startup ecosystem. These initiatives not only impacted technology-based startups but to any startup that has an influence of digitalization. The study also tries to examine factors like gender, age, number of family members, educational background, work experience, economic status and awareness about government’s digital initiatives that impacts decision to take entrepreneurship is a career. Quantitative research techniques are used by collecting data from budding and established entrepreneurs through questionnaires. The paper reviews the literature on enablers of startup ecosystem in India, challenges faced by entrepreneurs and role of government and their digital initiatives